WHAT EVERY PSYCHOLOGIST AND PSYCHOTHERAPIST SHOULD KNOW ABOUT THE PLACEBO AND NOCEBO EFFECT - Giacomuzzi , Salvatore; Ertl, Markus; Barinova, Natalia; Garber, Klaus; Kocharian , Alexander (Psychological Prospects Journal, 2021)
Purpose. Only a few medical terms are used as often, even in a metaphorically way, as the words placebo and nocebo. Almost any psychologist and psychotherapist think he/she knows well what by a placebo or nocebo is understood, but usually without really being able to explain it exactly and how it works. In addition, most psychologists and psychotherapists immediately think of clinical trials. However, many things are attributed to the placebo or nocebo effect that does not really fall under this concept in terms of a strict scientific terminology. Therefore, the following article summarizes the ongoing debate on placebo/nocebo effects by citing the current scientific literature.Methods. To realize the purpose of the study, we used the methods of theoretical scientific research.Results. In summary patients are more prone to develop nocebo effects are those with alternative or negative healthcare beliefs or experiences or unrealistic perceptions about treatment; managing these factors is a core strategy to counteract the nocebo effect. Conclusions. Healthcare professionals can help to minimise the influence of the nocebo effect by considering how information about treatments, including benefits and adverse effects, is framed and communicated. Establishing a positive interaction from the start and involving patients in decisions about their treatment and ensuring they understand the cause of their illness and what they can do to manage their symptoms is likely to lead to better treatment outcomes.
Keywords: placebo, nocebo, healthcare, patients, psychotherapist.